Exploração do trabalho infantil : violação de Direitos Humanos das crianças - Pereira, Nayara Toscano de Brito (2018)
The exploitation of child labor is a source of violation of the human rights of children, which entails profound changes in the organization of their lives, especially in the right to education, culture and leisure. The Child and Adolescent Statute (ECA) came into being in line with the Convention on the Rights of the Child, in order to deconstruct the culture of exploitation as something rooted in the national imagination, promoting a culture of integral protection for these developing people and conferring to them the status of social subjects and rights. In this context, this dissertation had as a guiding problem: in view of the context after the ECA, in what way the Service of Coexistence and Strengthening of Links has been implemented in João Pessoa from the perspective of the System of Guarantee of Rights of the Child and of the Teenager? The general objective was to analyze the Service of Coexistence and Strengthening of Links as a human rights policy that seeks to confront the exploitation of child labor based on the System of Guarantee of Rights of Children and Adolescents. To do so, we developed research with the Coexistence and Linkage Strengthening Service in five Social Assistance Reference Centers in João Pessoa (CRAS), as well as in the Specialized Reference Center for Social Assistance (CREAS). Semi-structured interviews were carried out with 7 subjects, so that we could verify if, in practice, the policy of confronting the exploitation of child labor is being carried out in the city. Data from the interviews were analyzed through a discourse analysis of Bardin, with regard to the 5 interviews with the CRAS Coordinators, and qualitative analysis of the interview with the CRAS State Coordinator and the State Reference Technique of the Strategic Actions of the Program Eradication Program Child labor. The results showed that, in general, there are strategic actions and services to prevent, combat and confront the exploitation of child labor, but some obstacles persist, such as the still precarious architectural structure and the reduced staffing, which implementation of such policies. This research points to the need for public policies on human rights to eradicate the exploitation of child labor, so we conclude that the services of CREAS and CRAS are fundamental in this process.